Volumetric Analysis of Amygdala, Hippocampus, and Prefrontal Cortex in Therapy-Naive PTSD Participants. (13th March 2014) - Starcevic, Ana; Postic, Srdjan; Radojicic, Zoran; Starcevic, Branislav; Milovanovic, Srdjan; Ilankovic, Andrej; Dimitrijevic, Ivan; Damjanovic, Aleksandar; Aksić, Milan; Radonjic, Vidosava
Abstract : Objective . In our study we have hypothesized that volume changes of amygdala, hippocampus, and prefrontal cortex are more pronounced in male posttraumatic stress disorder participants. Material and Methods . We have conducted a study of 79 male participants who underwent MRI brain scanning. PTSD diagnosis was confirmed in 49 participants. After MRI was taken all scans were software based volume computed and statistically processed. Results . We found that left amygdala is the most significant parameter for distinction between PTSD participants and participants without PTSD. There were no significant differences in volumes of hippocampi and prefrontal cortices. Roc curve method outlined left amygdala AUC = 0.898 (95% CI = 0.830–0.967) and right amygdala AUC = 0.882 (95% CI = 0.810–0.954) in the group of PTSD participants which makes both variables highly statistically significant. Conclusion . The present investigation revealed significant volume decrease of left amygdala in PTSD patients. Concerning important functions of the amygdala and her neuroanatomical connections with other brain structures, we need to increase number of participants to clarify the correlation between impared amygdala and possible other different brain structures in participants with PTSD.